2009
DOI: 10.1176/ps.2009.60.6.792
|View full text |Cite
|
Sign up to set email alerts
|

Approval Ratings of Inpatient Coercive Interventions in a National Sample of Mental Health Service Users and Staff in England

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Methods: A cross-sectional design was adopted. The Attitudes to Containment Measures Questionnaire (ACMQ) was completed by 1,361 service users and 1,226 staff in acute care mental health services from three regions of England. This provided evaluation of eleven coercive measures (e.g. seclusion) on six dimensions of approval (e.g. indignity, safety) in a large national sample. Comparisons betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(48 citation statements)
references
References 23 publications
(11 reference statements)
2
43
0
2
Order By: Relevance
“…Those that have considered ratings of acceptability have shown that staff rate seclusion as less acceptable than nearly every other form of containment and PICU care as one of the most acceptable forms of containment. 4 In our results, transfer to a PICU was rated as the most acceptable form of containment. However, seclusion was rated as less acceptable than transfer to a PICU, intermittent observations, constraint observation, PRN, time out and manual restraint.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Those that have considered ratings of acceptability have shown that staff rate seclusion as less acceptable than nearly every other form of containment and PICU care as one of the most acceptable forms of containment. 4 In our results, transfer to a PICU was rated as the most acceptable form of containment. However, seclusion was rated as less acceptable than transfer to a PICU, intermittent observations, constraint observation, PRN, time out and manual restraint.…”
Section: Discussionmentioning
confidence: 64%
“…53 Previous studies evaluating the acceptability and/or use of different containment methods in mental health services 4,45,54 have not considered the association between access to seclusion and/or PICUs and acceptability/use of different containment methods. Those that have considered ratings of acceptability have shown that staff rate seclusion as less acceptable than nearly every other form of containment and PICU care as one of the most acceptable forms of containment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The coercion, traumatizing procedure for the patient, has also a negative impact on the doctor-patient relation (Bonsack, Borgeat, 2007). Some studies followed the patient attitude towards coercion (Whittington et al, 2009), and its correct application in psychiatric care, using monitoring scales of the coercion measures throughout hospitalization (Swartz, Swanson, 2004). Isolation, coercion measure in psychiatry, is a managing the aggressive impulses measure of the patients with psychiatric impairments, as well as their psychomotor agitation.…”
Section: Fig 8 Entrapment Patient Distributionmentioning
confidence: 99%